PENERAPAN PROSEDUR TERAPI RELAKSASI BENSON DAN MUROTTAL AL-QUR’AN SURAH AR-RAHMAN AYAT 1-78 TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI PRIMER DI RSUD UNGARAN - Ns. Dwi Mulianda; Ela Lutfiatul Umah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
An increase in blood pressure that is not controlled will provide some further symptoms to organs such as the brain in the form of strokes, and heart in the form of coronary heart disease and hypertrophy. Benson relaxation and murottal Al-Qur'an surah Ar-Rahman ayat 1-78 is a nonpharmacological therapy that can reduce blood pressure in patients with primary hypertension so as to prevent further symptoms of hypertension. This case study aims is to discribe the application Benson relaxation and murottal Al-Qur'an surah Ar-Rahman ayat 1-78 to the reduction in blood pressure in patients with primary hypertension at RSUD Ungaran. The method of this study is descriptive. The subjects of this case study are two Moslem patients with hypertension who have no hearing problems. The data are collected through observation and measurement by using medical tools such as sphygmomanometer and stethoscope before and after the therapy. The result of this study shows that the blood pressure in subject I decreased blood pressure from 175/90 mmHg to 140/30 mmHg, while in subject II decreased blood pressure from 160/100 mmHg to 125/80 mmHg. The results of this case study reveal that the application Benson relaxation therapy and murottal Al-Qur’an surah Ar-Rahman ayat 1-78 shows the results of a decrease in blood pressure that is quite effective in patients with primary hypertension in RSUD Ungaran. Hopefully, Ungaran hospital can make Benson relaxation and Murottal Al-Qur'Aan relaxation surah Ar-Rahman ayat 1-78 as a basis for the development of nursing and companion of pharmacological therapy